Using transcriptomics to examine the physiological status of wild-caught walleye (Sander vitreus) - Jennifer D. Jeffrey; Matt J. Thorstensen; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Canadian Science Publishing, 2023)
Lake Winnipeg, Manitoba, is Canada's second largest commercial inland freshwater fishery, and concern over collapse of the walleye fishery is growing. Molecular techniques have been increasingly used to study responses of wild organisms to environmental and anthropogenic stressors. The present study used transcriptomics to examine the physiology of wild-caught walleye (Sander vitreus (Mitchell, 1818)) across Lake Winnipeg using non-lethal techniques. Gill transcriptomes of walleye sampled from the north and south basins of Lake Winnipeg, and the channel connecting them, exhibited distinct profiles implicating regionally specific biological responses. North basin walleye exhibited transcriptomic responses indicative of exposure to environmental stressors. Transcriptomic patterns suggested a shift to increased reliance on anaerobic metabolism and up-regulation of hypoxia-sensitive genes in north basin fish, possibly representing exposure to low-oxygen conditions. Exposure to environmental stressors may also have driven increases in gene transcripts associated with proteasomal catabolism, DNA repair, molecular chaperones, and ion regulation. North basin fish also exhibited transcriptomic patterns indicative of gill remodeling via regulation of the mTOR pathway, cytoskeleton reorganization, and fatty acid synthesis. Our results highlight the complexity of examining wild fish across environmental gradients but also the potential use of molecular techniques in elucidating organismal sensitivity to local environmental factors.